A Myth of Wereworl in Viking Wolf Movie (2022) - Inayah Inayah; Atinia Hidayah (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
This study aimed to analyze: (1) how the Viking Wolf movie (2022) presents the werewolf myth (2) how blod represents the transformation process of human into werewolf in Viking Wolf movie (2022). The study uses descriptive qualitative method to analyzed and described in descriptive form. In this research, applies Roland Barthes' semiotic theory as a grand theory and relevant source related to werewolf mythology. The object of research is myth of werewolf in the Viking Wolf movie (2022) directed by Stig Svendsen. The primary data used is a movie entitled Viking Wolf (2022) and also used supporting data from journals, books and other. The method of collecting data includes watching and reading, identifying, selecting, and classifying. The method of analyzing the data by displaying, explaining, and interpreting. The result of the study : (1) representation of the werewolf myth in Viking Wolf movie (2022), namely, the Vikings' obsession with animal power, the full moon; the culmination of mystical power and unchanged eyes symbolize human identity and human-like werewolf, (2) representation of blood in the transformation process of human into werewolf throught dreams in Viking Wolf movie (2022), namely, half-bloody; sensitive sense and changes habits and blood covers the body; animal instint and physical changes.